Profil Status Gizi Anak Pulau Di Desa Mattaro Adae, Kabupaten Pangkep - Rini Jusriani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Children who are malnourished cannot grow and develop optimally, which can reduce children's intelligence. The aim of this research is to determine the nutritional status profile of island children in Mattaro Adae Village, Pangkep Regency. This research is an analytical research by measuring the anthropometric nutritional status of elementary school children. The analysis used is chi-square. The research results showed that the BMI/U analysis obtained a mean value <SD, namely -3.46<0.517. Meanwhile, the frequency of island children who experienced normal BMI/U was 27 people (75%). The results of the TB/U analysis obtained a mean value<SD, namely -3.58<0.608. The frequency of children suffering from normal TB/U was 26 people (72.2%). The results of the BB/U analysis obtained a mean value<SD, namely -3.6<0.4. Meanwhile, the frequency of school children who experienced normal BB/U was 19 people (52.8%). BMI/U nutritional status was good in 8 year old children as many as 10 people (35.71%) and BMI/U nutritional status was poor in 5 year old children aged 7 years (62.5%). Meanwhile, the significance value or p value (paired) is 0.000, which shows that there is a relationship between age and nutritional status, BMI/U..